An Investigation into the Development of the Competencies of the Tunisian Entrepreneur: The Importance of International and Social Dimensions - Chouki, Mourad; Mnisri, Kamel; Hofaidhllaoui, Mahrane; Souissi, Ghassen (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
It is important to stress the importance of having the right competencies to sustain entrepreneurship initiatives in developing economies. Using a narrative approach based on the life stories of Tunisian entrepreneurs, this research aims to identify the entrepreneurial competencies developed over time and throughout the entrepreneurial journey. Our findings demonstrate the importance of social competencies that are related to the Tunisian context and the need for global entrepreneurial competencies framework. Furthermore, this research raises awareness about the challenges of the international context in entrepreneurship and the need to develop inter-cultural competencies, and elucidates the ambiguities surrounding required global entrepreneurial competencies.